2022
DOI: 10.3389/fnins.2022.851394
|View full text |Cite
|
Sign up to set email alerts
|

The Function of NF-Kappa B During Epilepsy, a Potential Therapeutic Target

Abstract: The transcriptional regulator nuclear factor kappa B (NF-κB) modulates cellular biological activity by binding to promoter regions in the nucleus and transcribing various protein-coding genes. The NF-κB pathway plays a major role in the expressing genes related to inflammation, including chemokines, interleukins, and tumor necrosis factor. It also transcribes genes that can promote neuronal survival or apoptosis. Epilepsy is one of the most common brain disorders and it not only causes death worldwide but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 161 publications
(199 reference statements)
0
17
0
Order By: Relevance
“…Moreover, our results showed that eugenol treatment suppressed the activation of NF-κB pathway, which has been considered a prototypical pro-inflammatory signaling pathway in the expression of several inflammatory cytokines, including TNFα and IL-1β. 40,41 These findings suggest that eugenol plays a neuroprotective role in SE-induced neuronal damage by alleviating reactive gliosis and enhancing the anti-inflammatory capacity.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, our results showed that eugenol treatment suppressed the activation of NF-κB pathway, which has been considered a prototypical pro-inflammatory signaling pathway in the expression of several inflammatory cytokines, including TNFα and IL-1β. 40,41 These findings suggest that eugenol plays a neuroprotective role in SE-induced neuronal damage by alleviating reactive gliosis and enhancing the anti-inflammatory capacity.…”
Section: Discussionmentioning
confidence: 88%
“…In epilepsy, activation of the NF‐κB pathway is upregulated in neurons, glial cells, and endothelial cells due to neuronal loss, glial cell proliferation, and blood–brain barrier dysfunction (Cai & Lin, 2022). As inflammation is one of the key features of epilepsy, seizures could induce the release of inflammatory factors, which could activate the NF‐κB pathway, and this activated NF‐κB signaling promotes their transcription to lead to inflammatory processes (Vezzani et al, 2008; Wang & Chen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In epilepsy, activation of the NF-κB pathway is upregulated in neurons, glial cells, and endothelial cells due to neuronal loss, glial cell proliferation, and blood-brain barrier dysfunction (Cai & Lin, 2022).…”
Section: Sirt3 Deficiency Increased Se-induced Inflammatory Responsementioning
confidence: 99%
“…Epileptogenesis is a complex pathological process involving mainly inflammatory responses and neuronal death [ 42 ]. The NF- κ B pathway is associated with inflammation and oxidative stress, plays a key role in epileptogenesis, and can regulate neuronal survival and apoptosis [ 43 ]. The IL-17 signaling pathway and TNF signaling pathway play a critical role in inducing blood-brain barrier disruption and CNS autoinflammation, which are closely associated with seizures [ 44 ].…”
Section: Discussionmentioning
confidence: 99%